SME Firm Performance-Financial Innovation and Challenges - Anthony, Abiodun Eniolaa; Harry, Entebang (Elsevier Ltd., 2015)
Without incertitude, SMEs have become the significant clout of sustained, instantaneous and bracing growth of Nigeria economy. Moreover, SMEs has performed an unparalleled role in advancing the Nigeria economic growth, and serve as a breeding ground for entrepreneurs and a provider of solutions to address the problems of unemployment in all consuming labours and promoting marketing growth. An opportunity for the healthy advancement of small and medium-sized enterprises (SMEs) in Nigeria was in relation to the transformation and expansion policy due to the brisk evolution of the global economy. But with the global economic integration, the small and medium-sized enterprises operating environment is facing tremendous changes and more intense competition. Hence, the reason for this paper is to present the sources of SME firm financing, conceptualize its financing challenges, source causes, with objectives to exploit the innovative ways to improve financing provision via crowdsourcing of financing and necessity to provide a regulatory environment that will support it for the growth and advancement of SMEs prospectively. Likewise, it is an essential strategy that would assist entrepreneurs to remain much motivated towards promoting his line of work. Moreover, it will reassure an individual to become a successful entrepreneur. This study will add to the existing literature in the academic area of entrepreneurship and at the same time offers a springboard that will provide an impulsion for empirical inquiry in this field. Besides, it offers important information and methods that would help entrepreneurs on how crowdfunding can serve as a source of financing provision and the positive impact on Small and medium enterprises (SMEs) firm performance.